Food Forage Potential and Carrying Capacity of Kemampo Forest Area with Special Objectives (KHDTK) as Sambar deer (Rusa unicolor) Captive Breeding Area - Fatahul Azwar; Burhanuddin Masy'ud; R Gartesiasih (Media Konservasi, 2019)
This research was carried out to identification and analysis of food forage diversity, productivity and carrying capacity of Kemampo special purpose forest area in South Sumatera as sambar deer captive breeding area. Diversity food forage for sambar deer were analysis systematically by using vegetation analysis with 10 units of square plot models for each growth level of vegetation with different size. Estimation of food forage productivity  were done by using 10 units of square plot models (1x1 m2) for each harvesting periode 20 days, 30 days and 40 days. Result of reseach was showed that there are 13 species of food forage has identification as sambar deer feed and five species among them were identification as urgent feed and high palatability for sambar deer, i.e Paspalum conjugatum, Imperata cylindrica, Acacia mangium, Vitex pubescens, dan Melastoma malabathricum. The avarage of food forage productivity for each harvesting periode 20 days, 30 days and 40 days were 48,40 kg/m2/day, 57,89 kg/m2/day and 62,78 kg/m2/day, with avarage value of food forage productivity  was  56,66 kg/m2/day or  152.982 kg/ha/year, and  458.946 kg/3 ha/year. According to this value of food forage productivity, and by using the assumptiom of dayly food need of sambar deer about 23 kg/head/day, so  the carrying capacity of Kemampo forest area were estimated about 13,968 individuals of sambar deer per 3 hectares per year or  per hectare  the area could retain everyday about 13 individuals of sambar deer. Keywords: rusa samsambar deer, food forage, productivity, carrying capacity, captive breeding